Flash heating boosts the potential for mechanochemical energy sources for subglacial ecosystems - Stone, Jordan; Edgar, John O.; Rutherford, Johnny; Gill-Olivas, Beatriz; Tranter, Martyn; Gould, Jamie A.; Xavier, Cijo M.; Telling, Jon (Frontiers in Geochemistry, 2023)
Subglacial environments harbour a diversity of microbial ecosystems capable of influencing biogeochemical cycles. However, the darkness and isolation of subglacial environments limit the energy sources available for microbial metabolism. A recently recognised energy source for these microbes in wet-based regions is the rock-water reactions that occur after the mechanical fracturing of glacial bedrock. These mechanochemical reactions produce H2 and H2O2 at 0°C from reactions with mineral surface defects (Si• and SiO•) and release Fe from within the mineral structures, providing electron donors and acceptors for microbial metabolism. However, the production of H2O2 and H2 may be underestimated as temperatures at rock abrasion sites can increase substantially above 0°C as glaciers “slip and grind” rocks, potentially accelerating the rates of mechanochemical reactions. Despite this, the effect of rapid heating on subsequent low-temperature mechanochemical reactions has yet to be examined. Here, we investigate H2, H2O2, and Fe production during low-temperature (0 °C) incubations of water with a range of ground rocks and minerals following “flash heating” to 30, 60, or 121 °C. We show that transient increases (as little as 5–10 min of heating) to moderate temperatures (30 or 60 °C) can significantly increase the rate of H2 production, while short-term heating to 121 °C generates larger bursts of H2. In addition, pyrite is easily crushed, potentially releasing large quantities of Fe2+ into subglacial systems and promoting mechanochemical reactions due to the resulting large surface area (10× larger than other materials). We provide the first evidence for H2 production from water reactions with crushed pyrite and suggest that crushed pyrite has a greater influence on subglacial H2O2 production than silicates. We conclude that electron donors in the form of Fe2+ and H2 bursts can be produced in subglacial ecosystems, which may be coupled to substantial concentrations of H2O2 produced from crushed pyrite. This suggests that rock–water mechanochemical reactions may be a greater source of energy for subglacial environments than previously recognised.